ASSESSING THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT IN ENHANCING BUSINESS EDUCATORS’ COMMITMENT IN SOUTH SOUTH NIGERI - Abasi, Ekemini Udoette; Ibe, Chinedu Emmanuel; Okereke , Chukwudi Ifeanyi (International Research Journal of Arts and Communication, 2024)
This study was conducted to assess the influence that perceived organization support (POS) has on commitment of business educators in federal tertiary institutions in south-south, Nigeria. Survey research design was adopted for the study. Population for the study was 92. Owing to the small number, the entire population was used as the sample size. Data for the study was sourced from both primary and secondary source. Primary source was from administered copies of questionnaire. Research instrument was a structured Likert scale questionnaire. Descriptive statistics and simple linear regression statistical tools were used in analyzing the collated data. Findings revealed that fairness had a moderated correlation value of R=0.519 with a standardized coefficient β=0.418. Supervisor support showed a standardized coefficient of β=0.536. Conclusively, perceived organizational support has a significant positive influence on the commitment of business educators in federal tertiary institutions in south-south, Nigeria. Since POS is seen as the extent to which the organization values the employees’ contribution and cares about their well-being, it is believed that the employees should reciprocate such perceived support with increased commitment, loyalty and performance.